(untitled) (Research, Society and Development, 2023)
The objective of the study was to evaluate the levels of salivary Cortisol and Alpha-amylase, relating them to the level of stress and academic performance of freshmen of the Nursing course, during the first practical evaluation of the Human Anatomy discipline. Saliva collection procedures were performed before and after the application of the practical assessment of Human Anatomy. Salivary Cortisol and alpha-amylase concentrations were evaluated by the ELISA method. The short version of the Stress Assessment Questionnaire in Nursing Students was used. Results: It was observed that the mean concentration of salivary cortisol was 0.421 ± 0.076 µg/dL and the final one was 0.572 ± 0.096 µg/dL, characterizing a significant increase of 35.8% (p<0.0001). Similar results were observed for salivary alpha-amylase concentrations (Initial: 100.70 ± 7.37 U/mL and Final: 135.64 ± 10.85 U/mL), with a significant increase of 34.7% in the concentration (p<0.0001). The evaluation index made it possible to identify three explanatory factors (behavioral, stressors and organizational). For the explanatory stressor factor, a moderate level was observed in 53% of the sample. Furthermore, a high level of stress regarding the organizational explanatory factor was observed in 80%. An average peak of cortisol of 36.5 ± 9.6% (Final - Initial %) and percentage of academic performance of 75.9 ± 16.4% were observed, which demonstrates the negative influence of the percentage of stress levels on the performance of the participants . Conclusion: Anxiety before evaluation exams generates negative results in the performance of academics.